Dosimetric Verification of Grid Radiotherapy Using Three Ionization Chamber Detectors o Dosimetry - Alanizy, Najah A.; Attalla, Ehab M.; Abdelaal, Ahmed M.; Yassen, Mohamed N.; Shafaa, Medhat W. (Iraqi Journal of Science, 2022)
This study aims to provide verification between measured and calculated radiation dose using three different ionization chamber detectors in Grid plans to select the best ones To the best of our knowledge, this is the first practical experiment in such subject. Grid radiotherapy is an unconventional method for bulky tumors treatment. It is characterized by a single-fraction and high radiation dose. Ten cases (scenarios) were selected to achieve Grid plans by MLCs, with a single dose of 1500-2000 cGy. Three ionization detectors were employed to measure the maximum, mean, and point doses (cGy), and match them with those calculated by the linear accelerator used in this study. The results showed significant differences among the three detectors in measuring the maximum and mean doses, with p-value = 0.0016 and 0.06, respectively. While the differences among the measured three detectors and calculated doses for the point dose were non-significant, p = 0.12. The variation in the results of the corresponding percentage between calculated and measured doses depended on the type and position of the detector, the scattering, and the leakage of the radiation. In conclusions, the Semi-flex chamber gives the best results.